Urgensi Keamanan Pangan Rumah Tangga dalam Menghadapi Pandemi Covid-19 - Noni Setyorini; Efriyani Sumastuti; Ratih Hesty Utami (Jurnal Sosial Ekonomi Pertanian, 2022)
Abstract This study aims to examine the urgency of household food safety in the face of the Covid-19 pandemic. The data was collected using an online survey with simple random sampling technique.   The  number   of  respondents collected   was  135  respondents.   Data processing was carried out by SEM-PLS using the SMART PLS software. Based on the results of data processing, household expenditure has an effect on food safety. Nutritional knowledge variables also affect response toward pandemic. Access to food has a negative and significant effect on household expenditure. Household characteristics on access to food also have a  significant negative effect. This research provides theoretical and practical contributions which will also be discussed further in this paper. Keywords:        Food safety, covid-19, food access, household contest, pandemic response, nutrition knowledge, household characteristics.